The Importance of Transportation Policy in Addressing Globalization - Feby Lamtiar Simanjuntak; Lubna Salsabila; Timbul Dompak; Karol Teovani Lodan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Transportation is a vital part of political, economic, socio-cultural, and defense and security life. Transportation plays a role as a means of improving the integrity of the nation and raising the standard of living of the community as a whole. As a result, globalization is the process by which each action increases the value of specific communities. Transportation is essential in many ways. Transportation contributes to the improvement of the nation's integrity and the general improvement of the community's standard of living. In general, transportation is a tool that makes it easier to achieve goals that help the economy of a region grow and a force that brings people together in the Unitary State of the Republic of Indonesia. The type of research used in this study is qualitative research with a descriptive approach. This research will look into previous literature related to the transportation system in Indonesia to see the policy implementation pattern in Indonesia. The result shows that a good transportation policy might influence congestion levels and lead a nation closer to sustainable development.